2005
DOI: 10.1111/j.1399-0012.2005.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the treatment and management of new‐onset diabetes after transplantation1

Abstract: Although graft and patient survival after solid organ transplantation have improved markedly in recent years, transplant recipients continue to experience an increased prevalence of cardiovascular disease (CVD) compared with the general population. A number of factors are known to impact on the increased risk of CVD in this population, including hypertension, dyslipidemia and diabetes mellitus. Of these factors, new-onset diabetes after transplantation has been identified as one of the most important, being as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
175
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(182 citation statements)
references
References 33 publications
0
175
0
7
Order By: Relevance
“…The consensus guidelines advise that screening for disorders of glucose homeostasis in established (Ͼ1 yr) RTR should be performed on an annual basis, in keeping with current American Society of Transplantation recommendations (16). The oral glucose tolerance test (OGTT) is not recommended as a screening tool in RTR, although it is suggested that it should be performed in all RTR with FBG of Ն110 mg/dl (6.1 mmol/L) (17). In liver transplant recipients, the OGTT has been advocated as an annual screening tool in all individuals with a normal FBG (18).…”
mentioning
confidence: 99%
“…The consensus guidelines advise that screening for disorders of glucose homeostasis in established (Ͼ1 yr) RTR should be performed on an annual basis, in keeping with current American Society of Transplantation recommendations (16). The oral glucose tolerance test (OGTT) is not recommended as a screening tool in RTR, although it is suggested that it should be performed in all RTR with FBG of Ն110 mg/dl (6.1 mmol/L) (17). In liver transplant recipients, the OGTT has been advocated as an annual screening tool in all individuals with a normal FBG (18).…”
mentioning
confidence: 99%
“…22 Per the 2003 International Consensus Guidelines for new-onset diabetes after transplant, weekly fasting plasma glucose screening is recommended for the first month after OLT, followed by screening at 3, 6, and 12 months and annually thereafter. 29,30 Hemoglobin A 1c may not be accurate in the early posttransplant period owing to anemia and high red blood cell turnover. The diagnosis of diabetes is the same as in the general population.…”
Section: Article Highlightsmentioning
confidence: 99%
“…Some studies have shown higher incidence of infection in diabetic cardiac transplant patients compared to nondiabetic patients [129]. Discrepancies in the results of these studies are attributed to the limitations including defining criteria for the diagnosis of diabetes, therapeutic regimen used for the management of diabetes, target glycemic control and presence of any associated micro or macrovascular complications of diabetes [131,137,138]. Further studies are required to define the therapeutic targets and impact of glycemic control on development and prognosis of CAV.…”
Section: Diabetes Mellitusmentioning
confidence: 99%